Kearns–Sayre Syndrome Minus: Two Cases of Identical Large-Scale Mitochondrial DNA Deletions with Presentations outside the Classical Triad - Shir Wey Gloria Pang; Hencher Han Chih Lee; Carol Ng Wing kei; Eric Kin Cheong Yau; Joannie Hui (Case Reports in Genetics)
A curious triad of retinitis pigmentosa, external ophthalmoplegia, and complete heart block was presented by Sayre et al. in 1958. Since then, the disorder named Kearns–Sayre syndrome (KSS) has come to represent patients with mitochondrial DNA deletions presenting before adulthood, primarily with chronic progressive external ophthalmoplegia (CPEO) and pigmentary retinopathy. However, it is increasingly noted that the presentations can well be variable despite similar genetic deletions. Here, we present two cases with identical large-scale mitochondrial DNA deletions but very dissimilar outlook.